Musculoskeletal pain in patients with chronic kidney disease - Francisco Caravaca; Boris Gonzales; Miguel Ángel Bayo; Enrique Luna (Nefrología (English Edition), 2016)
Introduction: Chronic musculoskeletal pain (CMP) is a very common symptom in patients with chronic kidney disease (CKD), and is associated with a significant deterioration in quality of life. Aims: To determine the prevalence and clinical characteristics associated with CMP in patients with advanced CKD not on dialysis, and to analyse their relation with other uraemic symptoms and their prognosis significance. Materials and methods: Cross-sectional study to analyse the uraemic symptoms of an unselected cohort of patients with CKD stage 4–5 pre-dialysis. In order to characterise patients with CMP, demographic and anthropometric data were collected, as well as data on comorbidities and kidney function. In addition, inflammatory parameters, uric parameters, bone mineral metabolism including 25-hydroxycholecalciferol (25-OHCC), creatine kinase and drugs of potential interest including allopurinol, statins and erythropoiesis-stimulating agents were recorded. Results: The study group consisted of 1169 patients (mean age 65 ± 15 years, 54% male). A total of 38% of patients complained of CMP, and this symptom was more prevalent in women than in men (49 vs. 28%; P < .0001). Muscle weakness, pruritus, muscle cramps, ecchymosis, insomnia, oedema and dyspnoea were the most common symptoms associated with CMP. There were no significant associations between serum levels of creatine kinase, 25-OHCC, treatment with allopurinol, statins or erythropoiesis-stimulating agents and CMP. The female gender, elderly age, obesity, comorbidity (mainly diabetes, heart failure or COPD), and elevated levels of inflammatory markers (C-reactive protein and non-neutrophilic leukocytes) were the best determinants of CMP. While patients with CMP showed a worse survival rate, a multivariate analysis adjusted for demographic data ruled out the independent association of CMP with mortality. Conclusions: CMP is highly prevalent in patients with advanced CKD and is associated with other common symptoms of chronic uraemia. As with the general population, elderly age, the female gender, obesity and some comorbid conditions are the best determinants of CMP. Increased inflammatory markers commonly observed in patients with CMP may have a relevant role in its pathogenesis.